Uji Toksisitas Makroskopis Pada Organ Ginjal, Hati, Jantung dan Limpa Mencit Hiperglikemia yang Diberi Ekstrak Etanol Kulit Buah Rambai (Baccaurea motleyana) - Ria Ceriana; Dwi Putri Rejeki (Journal of Pharmaceutical and Health Research, 2023)
Diabetes mellitus (DM) is a group of metabolic diseases characterized by hyperglycemia. Plants that can reduce blood sugar levels in alloxan-induced mice are Rambai peel (Baccaurea motleyana). The safety of the use of plants as herbal medicine must be known so as not to cause unwanted harmful effects. In this study, the relative weight of organs and changes in organ appearance were observed macroscopically. The design in this study was a completely randomized design with 24 male mice divided into 6 treatments and 4 replications. The treatment consisted of a negative control (Aquadest), a positive control (glibenclamide), peel Rambai ethanol extract with graded doses of 200 mg/kg, 400 mg/kg, 800 mg/kg and 1600 mg/kg. , given orally. The results showed that the ethanol extract of Rambai peel had no significant effect on the relative weight of the heart, kidneys and spleen, but had a significant effect on the relative weight of the liver. The results of this study also showed that no color changes were seen in any of the mice organs. So, this study showed no visible macroscopic changes in the organs, so that administration of Rammbai ethanol extract gradually causes fewer toxic effects and is still considered safe in experimental animals.